The Factors Associated with Late Arrival Among Stroke Patients: a Sistematic Review - ubleeuw, Irianti; Anna, Annastasia; prawesti, Ayu (Universitas Malahayati, 2025)
ABSTRACT Delayed arrival of stroke patients at the hospital is a major factor causing delays in stroke management, every 60-minute delay in the arrival of stroke patients at the hospital has the potential to increase short-term mortality significantly. This study aims to identify factors associated with delayed arrival of patients at the hospital. This research used the systematic review method with keywords “related factors OR related factor OR associated factor” AND “late arrival OR delayed arrival” AND “stroke or acute stroke or ischemic stroke” by including all full-text primary studies written in English and published between 2013 to 2024 from four databases, EBSCO-host, PubMed, and Scopus, EBSCO (Cinahl), Science Direct, and two e-resources, Google Scholar and Sage Journals. Twenty-nine articles were obtained from 7280 articles that discussed the causes of stroke patients' delayed arrival. There were six causes of delayed arrival: Socio-Demographic Factors, Knowledge and Awareness Factors, Family and Social Support Factors, Transportation and Distance Factors, Health System Factors, and Patient Perception of Stroke Condition Factors.Overall, this systematic review identifies factors contributing to delays, including socio-demographic aspects, knowledge, family support, transportation, patient perception, and health system readiness. Addressing these factors through education, infrastructure improvements, and enhancing healthcare service readiness can help accelerate patient arrival at the hospital and improve stroke treatment outcomes. Keywords: Delayed arrival, Pre- Hospital, Stroke